Call Me Maybe… A Simulation Based Curriculum for Telephone Triage Education in a Pediatric Residency - Blumberg, Joel S.; Barajaz, Michelle; Roberts, Danielle; Clary, Cody; Kumar, Shelley (Frontiers in Pediatrics, 2020)
Pediatrician communication with caregivers by phone has traditionally made a significant impact on patient care but remains a source of medical liability. Despite its importance, few publications exist regarding the education of pediatric residents on telephone triage. Our study involved the development of an educational curriculum aimed at expanding the pediatric resident skill set in telephone triage. Our method of curriculum development is based on Kolb's experiential learning theory. We utilized a combination of resource familiarization, didactic education, and simulation in the building of knowledge through reflection upon concrete experience, generalization of knowledge gained, and application of this new knowledge. We developed a 30-min PowerPoint presentation in which instructors reviewed the basic tenets of telephone triage. In the pilot study, residents were divided into two groups—a didactic-first group and a simulation-first group. Their performance was monitored during two scripted, symptom based “parent” phone call simulations. The didactic-first group received the PowerPoint didactic prior to the simulation, and the simulation-first group received the didactic after the simulation. A comparison of resident evaluations by faculty and self-documented confidence level revealed statistically significant higher evaluation scores in the didactic-first group, and an overall improvement in resident confidence with telephone triage. We conclude that this educational curriculum may improve pediatric resident performance in telephone triage.